2019
DOI: 10.1080/10942912.2019.1600543
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and antioxidant activity of wheat bran and barley husk in the extracts with different polarity

Abstract: Extracts of wheat bran and barley husk with solvents of different polarity were analyzed to determine the concentration of bioactive compounds (phytic acid, saponins, flavonoids, total phenolic compounds and phenolic profile) and their antioxidant activity by DPPH and ABTS assays. The results showed that the phytic acid concentration in wheat bran was higher than the phytic acid concentration in barley husk. The concentration of saponins was inverse with higher concentrations in barley husk than wheat bran. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 54 publications
(65 reference statements)
2
22
2
2
Order By: Relevance
“…Distribution of ferulic acid as a major contributor to the antioxidant activity was unevenly balanced within decreased order from Bran > Shorts > C3-C1 > B1 > B2-B3. Many authors confirmed that ferulic acid distribution in cereals varied within the kernel where the highest content remains in the outer layers and lowest in the endosperm [53][54][55].…”
Section: Phenolic Acids In Milling Fractionsmentioning
confidence: 94%
“…Distribution of ferulic acid as a major contributor to the antioxidant activity was unevenly balanced within decreased order from Bran > Shorts > C3-C1 > B1 > B2-B3. Many authors confirmed that ferulic acid distribution in cereals varied within the kernel where the highest content remains in the outer layers and lowest in the endosperm [53][54][55].…”
Section: Phenolic Acids In Milling Fractionsmentioning
confidence: 94%
“…The Maillard reaction often occurs along with other reactions and processes. The increasing of antioxidant activity could be the result of synergistic interactions between phenols and compounds such as carbohydrates and proteins in samples (López-Perea et al., 2019; Xu et al., 2020). The presence of a large amount of sugar also increases antioxidant activity, since soluble carbohydrates can act synergistically with phenolic compounds and increase antioxidant activity (Xu et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The extracts of the free and complex phenolic compounds were used to measure total phenolic content and antioxidant activity by the 2,2-diphenyl-1-picrylhydrazyl hydrate (DPPH) and 2,2'-azino-bis (3-ethylbenzothiazoline-6sulfonic acid) (ABTS) radicals. Both of these assays were previously described in López-Perea et al (2019).…”
Section: Methodsmentioning
confidence: 99%